Էնվեր փաշայի՝ բոլշևիկների հետ համագործակցության հարցի շուրջ - Ա. Է. Մելքումյան (ՀՀ ԳԱԱ հրատ.)
В 1919-1922 гг. большевики вступили в контакт с Энвером пашой – бывшим военным министром Османской империи и одним из организаторов геноцида армян. Руководствуясь собственными интересами, большевики оказали финансовую поддержку Энверу паше. In 1919-1922 the Bolsheviks entered into contact with Enver Pasha, a former Ottoman military minister and one of the organizers of the Armenian Genocide. Guided by their own interests, the Bolsheviks provided financial support to Enver Pasha.
Keywords: History; Political Science; Modern History; D History; J Political Science